METHODOLOGY FOR DEVELOPING STUDENTS’ CREATIVE ABILITIES THROUGH PHYSICAL EDUCATION TOOLS (Sciental Journal of Education Humanities and Social Sciences, 2025)
This article provides an analytical overview of the levels and possibilities of expressing creative activity during physical movement. It emphasizes individual characteristics of motor activity and focuses on the conscious and unconscious levels of creativity in physical performance. It substantiates the development of students’ creative abilities through physical movement activities.